2011
DOI: 10.1111/j.1467-9515.2010.00752.x
|View full text |Cite
|
Sign up to set email alerts
|

What are Children's Centres? The Development of CC Services, 2004–20081

Abstract: Children's centres are intended to be a mainstream, universal service. They began in 2004 and their origins are diverse. Some replaced various forms of local provision, most notably Sure Start programmes; others were established from scratch. Issues for exploratory empirical work have been identified from the guidance issued by central government. Using interview data from three urban local authorities, this article explores the nature of the 'core offer' that centres are expected to provide and the way in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…However, only three studies assessing the impact of child care were identified in this review. Previous reviews - based on intervention descriptions - found that children’s centres were increasing in number in the UK, as part of a strategy of social investment [ 61 , 62 ]. Studies by Melhuish and colleagues found that high quality children’s centres appeared to reduce socioeconomic inequalities, as children from less advantaged backgrounds benefited more than those from more advantaged backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…However, only three studies assessing the impact of child care were identified in this review. Previous reviews - based on intervention descriptions - found that children’s centres were increasing in number in the UK, as part of a strategy of social investment [ 61 , 62 ]. Studies by Melhuish and colleagues found that high quality children’s centres appeared to reduce socioeconomic inequalities, as children from less advantaged backgrounds benefited more than those from more advantaged backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…It encouraged involvement to promote positive management skills and self - regulation. Other previous studies illustrated ways in which parenting activities delivered across income groups [8, 11] were not limited to cognitive gains, but also included physical, social, and emotional gains, all of which are determinants of health over the life course [12, 23, 2830]. However, while focusing on parenting is important, it is also necessary to address the conditions of daily life which make positive parenting difficult.…”
Section: Discussionmentioning
confidence: 99%
“…It encouraged involvement to promote positive management skills and self -regulation. Other previous studies illustrated ways in which parenting activities delivered across income groups [8,11] were not limited to cognitive gains, but also included physical, social, and emotional gains, all of which are determinants of health over the life course [12,23,[28][29][30]. However, while focusing on parenting is important, it is also necessary to address the conditions of daily life which make positive parenting difficult.…”
Section: Discussionmentioning
confidence: 99%